Media and the American child - Comstock, George A. (Educational psychology., 2007)
This new work summarizes the research on all forms of media on children, looking at how much time they spend with media everyday, television programming and its impact on children, how advertising has changed to appeal directly to children and the effects on children and the consumer behavior of parents, the relationship between media use and scholastic achievement, the influence of violence in media on anti-social behavior, and the role of media in influencing attitudes on body image, sex and work roles, fashion, & lifestyle. The average American child, aged 2-17, watches 25 hours of TV per week, plays 1 hr per day of video or computer games, and spends an additional 36 min per day on the internet. 19% of children watch more than 35 hrs per week of TV. This in the face of research that shows TV watching beyond 10 hours per week decreases scholastic performance. In 1991, George Comstock published Television and the American Child, which immediately became THE standard reference for the research community of the effects of television on children. Since then, interest in the topic has mushroomed, as the availability and access of media to children has become more widespread and occurs earlier in their lifetimes. No longer restricted to television, media impacts children through the internet, computer and video games, as well as television and the movies. There are videos designed for infants, claiming to improve cognitive development, television programs aimed for younger and younger children-even pre-literates, computer programs aimed for toddlers, and increasingly graphic, interactive violent computer games. *Presents the most recent research on the media use of young people *Investigates the content of children's media and addresses areas of great concern including violence, sexual behavior, and commercialization *Discusses policy making in the area of children and the media *Focuses on experiences unique to children and adolescents.